Language and Self-Interest: Preliminary Notes Towards a Public Choice Approach to Legal Language - Jonathan R. Macey (Washington University Law Quarterly, 1995)
In this Article I will give a few examples of this phenomenon in action. I will begin with a benign example, in which no damage is caused by a failure to understand the true purpose of the speaker's words. I will then move to some examples in which, it might be argued, real harm is caused by the failure to understand the true purpose of the communication. Finally, I will explain why language is used in the way I am describing in this essay.
Keywords: Linguistics